Functionalization of bacterial cellulose wound dressings with the antimicrobial peptide ε-poly-L-Lysine. (30th January 2018) - Fürsatz, Marian; Skog, Mårten; Sivlér, Petter; Palm, Eleonor; Aronsson, Christopher; Skallberg, Andreas; Greczynski, Grzegorz; Khalaf, Hazem; Bengtsson, Torbjörn; Aili, Daniel
Abstract: Wound dressings based on bacterial cellulose (BC) can form a soft and conformable protective layer that can stimulate wound healing while preventing bacteria from entering the wound. Bacteria already present in the wound can, however, thrive in the moist environment created by the BC dressing which can aggravate the healing process. Possibilities to render the BC antimicrobial without affecting the beneficial structural and mechanical properties of the material would hence be highly attractive. Here we present methods for functionalization of BC with ε -poly-L-Lysine ( ε -PLL), a non-toxic biopolymer with broad-spectrum antimicrobial activity. Low molecular weight ε -PLL was cross-linked in pristine BC membranes and to carboxymethyl cellulose functionalized BC using carbodiimide chemistry. The functionalization of BC with ε -PLL inhibited growth of S. epidermidis on the membranes but did not affect the cytocompatibility to cultured human fibroblasts as compared to native BC. The functionalization had no significant effects on the nanofibrous structure and mechanical properties of the BC. The possibility to functionalize BC with ε -PLL is a promising, green and versatile approach to improve the performance of BC in wound care and other biomedical applications.